Golden share and privatization: between public and private interest (Revista Direito em Debate, 2022)
The paper analises the paradigm change in reference of economic intervention by Brazilian State, from interventionist to regulator, special from Federal Constitution of 1988. It is studied, as well, the privatization phenomenon of public companies and mixed-capital companies caused by neoliberalism, in special Embraer and Vale privatizations in the 90’s. The golden share is comprehended, your characteristics and peculiarities and how this share works as public interests instrument defender in privatized companies. For the present paper, we used exploratory nature of qualitative research and bibliography and documentary research technique.